PATTERNS OF ARGUMENT CONSTRUCTION IN TOASTMASTERS' COMPETITIONS: what we can learn from the champions - Intan Ayuning Tyas, - (2023)
Public speakers commonly construct their arguments by utilizing the layout of arguments in order to give a compelling argument in a speech. Given the significance of creating a compelling argument, this study aims to identify the layout of the arguments used by ten Toastmasters Champions as well as the ground data they dominantly used to persuade their audience. This study used a qualitative case study method to examine the data. Ten YouTube videos from the Toastmasters International channel as the data sample. The data were next transcribed and examined using Toulmin's (2003) theory regarding the layout of arguments and the supported theory from Hitchcock (2005) about types of data. The findings demonstrate that one layout of an argument-the first layout of arguments that contains: claims, data, and warrant-is dominantly used by speakers. This study also finds that one type of data that typically serves as a foundation for the claim is presented in the form of stories. The findings suggest that simplicity is preferred by the speakers as it is essential for understanding and influence.